PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP MOTIVASI KERJA DAN DAMPAKNYA TERHADAP KINERJA KARYAWAN PADA PT ASURANSI PAROLAMAS CABANG PEKANBARU - Nizamil Fadly (Universitas Negeri Medan, 2017)
This study aims to determine and analyze the influence of Leadership and compensation on work motivation and its implications on the employees performance of PT Asuransi Parolamas Pekanbaru Branch. Population and sample of this research are all employees of PT Asuransi Parolamas Pekanbaru branch, amounting to 101 employees. The type of data using primary data, method of data collection using questionnaires and interviews. Analysis of the data based on the description of a variable that contains a statement in the form of a questionnaire given to employees of PT Asuransi Parolamas Pekanbaru result that the Leadership, Compensation and motivation affects employee performance in PT Asuransi Parolamas Pekanbaru, validity and reliability showed that the variables Leadership, Compensation, Motivation and Performance valid and reliable for subsequent analysis. Path analysis for linear regression analysis on the first level where all variables are positive effect obtained linear regression first level as follows: Y1 = 0.315X1 + 0.584X2+ 0.227є and the ability of leadership and compensation variables in explaining the variations that occur in the variable involvement at 77.3% , multiple linear regression second level, Y2 = 0,092X1 + 0.041X2 + 0.375 Y1 +0.021є and the ability variables leadership, compensation and motivation in explaining the variations that occur in the variable engagement by 97.9%. Partial test (t test) where variable signifikan Leadership and Compensation influential on motivation and leadership and motivation Job significant effect on the performance of employees of PT Asuransi Parolamas because the level of sign less than 0.05. whereas compensation does not affect the performance of employees of PT Asuransi Parolamas Pekanbaru Branch for sign> 0.05. Keywords: Leadership, Compensation, Employee Motivation and Work Performance